2013
DOI: 10.9734/bjmmr/2013/2144
|View full text |Cite
|
Sign up to set email alerts
|

Breakfast Habits and Family Structure Associated with Overweight and Obesity in General Basic Students, Ecuador

Abstract: Aim: This study aimed to characterise the consumption and type of breakfast associated with overweight and obesity in students of the Quito Metropolitan area in the academic year 2010-2011. Study Design: Cross sectional study. Place and Duration of Study: Quito municipal schools during the academic year 2010-2011. Methodology: We surveyed 6964 students (3254 males, 3710 females; age range 9

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Similarly, the association between toxic habits and dieting could be interpreted as an increase in toxic habits among school children who report dieting. In 2012 we published, for this group of pupils, the association between excess weight and not breakfasting, as it was found that the crude OR for weight excess and not breakfasting of 1.44 (CI 95% 1.16 -1.80) was strengthened after adjustment by age, sex, family type, family stage, sedentarism and health zone: OR 1.54 (CI 95% 1.16 -2.05) [15].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the association between toxic habits and dieting could be interpreted as an increase in toxic habits among school children who report dieting. In 2012 we published, for this group of pupils, the association between excess weight and not breakfasting, as it was found that the crude OR for weight excess and not breakfasting of 1.44 (CI 95% 1.16 -1.80) was strengthened after adjustment by age, sex, family type, family stage, sedentarism and health zone: OR 1.54 (CI 95% 1.16 -2.05) [15].…”
Section: Discussionmentioning
confidence: 99%
“…(6,7) The causes of the increasing prevalence rates of overweight and obesity in children and adolescents are mainly associated with an increased caloric intake and reduced physical activity levels. (8,9) Regarding other associated factors, Orban et al (10) report that the family environment is associated with the development of these conditions, since it influences children and adolescents' food intake habits and lifestyles, and Romero et al (11) and Azar et al (12) state that social determinants such as the neighborhood characteristics and the socioeconomic level are related to the occurrence of these disorders in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Details of the study design may be found in publications which derived from it. [13][14][15] The overall prevalence of excess weight found was 26.6% (CI95% 25.8-27.4), varying with sex and age. 13 Attending a school belonging to a low-income city administrative district, being from a nuclear family (father, mother and children), eating alone, following a diet, not breakfasting, eating fast-food and sedentarism were all associated with excess weight.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] The overall prevalence of excess weight found was 26.6% (CI95% 25.8-27.4), varying with sex and age. 13 Attending a school belonging to a low-income city administrative district, being from a nuclear family (father, mother and children), eating alone, following a diet, not breakfasting, eating fast-food and sedentarism were all associated with excess weight. 14 Within this line of analysis, and given the fundamental role of parents in children's acquisition of eating habits, we invited the parents of the students to participate, with the aim of investigating agreements and discrepancies between them in responding to the same questions.…”
Section: Introductionmentioning
confidence: 99%